2011
DOI: 10.1186/1471-2458-11-556
|View full text |Cite
|
Sign up to set email alerts
|

Inherent illnesses and attacks: an ethnographic study of interpretations of childhood Acute Respiratory Infections (ARIs) in Manhiça, southern Mozambique

Abstract: BackgroundPneumonia is a leading cause of childhood hospitalisation and child mortality in Africa. This study explores local interpretations of Acute Respiratory Infections (ARIs), focusing on caretakers of children under five in the context of hospital care seeking.MethodsThe study took place in Manhiça, southern Mozambique and used Focused Ethnographic Study tools (FES) including field exercises and interviews.ResultsUnderstandings of terms used to describe ARIs differed between caretakers and hospital staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…In this setting, the hospital was viewed by the respondents as a “well-intentioned” entity, and their trust and obedience towards the health system, expressed by the term “the rule of hospital”, is consistent with findings from previous studies in the same setting [30], [37]. Interestingly, despite the presence of informal drug vendors and other sources of anti-malarial drugs in the study area, the study participants only trusted the formal health system for prescribing drugs to pregnant women.…”
Section: Discussionsupporting
confidence: 86%
“…In this setting, the hospital was viewed by the respondents as a “well-intentioned” entity, and their trust and obedience towards the health system, expressed by the term “the rule of hospital”, is consistent with findings from previous studies in the same setting [30], [37]. Interestingly, despite the presence of informal drug vendors and other sources of anti-malarial drugs in the study area, the study participants only trusted the formal health system for prescribing drugs to pregnant women.…”
Section: Discussionsupporting
confidence: 86%
“…A number of studies have demonstrated, similar to our findings, that illness interpretations and care-giving strategies are a deeply social affair and often developed through ongoing consultation within a caregiver’s lay referral network [10, 12, 26, 27]. A mother’s husband, extended family, and neighbors were influential in her lay referral network that also assisted in minimizing uncertainties associated with childhood illness and care-seeking.…”
Section: Discussionsupporting
confidence: 82%
“…Although the hospital is viewed as an entity of trust and obedience towards the health system in most of the communities [25], in this setting, the health care staff were viewed by the respondents as a “well-intentioned” during antenatal consultations. However, most of the pregnant women mentioned having simply taken the tablets without an explanation about what those tablets were for.…”
Section: Discussionmentioning
confidence: 99%